10h+4=-2

Simple and best practice solution for 10h+4=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10h+4=-2 equation:


Simplifying
10h + 4 = -2

Reorder the terms:
4 + 10h = -2

Solving
4 + 10h = -2

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + 10h = -2 + -4

Combine like terms: 4 + -4 = 0
0 + 10h = -2 + -4
10h = -2 + -4

Combine like terms: -2 + -4 = -6
10h = -6

Divide each side by '10'.
h = -0.6

Simplifying
h = -0.6

See similar equations:

| X^2+2x-31=-7 | | x^2+y^2+2x-16y+16=0 | | (x/4.5)+2.8=7.9 | | (2y^2-4y)-(-y^3+2)=0 | | B^1/2+3b^1/4-10=0 | | 4x(3-x)=28 | | 8-(3z-8)=2-4z | | -5+(-15d+1)=2(70-16)-d | | (2c-5)(c+6)+(c+6)(3c-2)= | | .33h-3-.75h=2 | | 2.2k-1.9=10.7 | | x+(1/2)=(3/4) | | 1.1k+3.7=8.1 | | 3x=59049 | | 3(3+x)=2(x-4) | | 5+(m/7)=10 | | 2n+5=4n+8-1n | | .66(6x-27)=-4 | | -7b+112=0 | | 2y(2x+3y)= | | 2x+4=8y+12 | | (10+-4)2= | | 3/8(m-2/9)=4.75 | | 3.3(1.2x+.5)=9.87 | | 2y-1-7y=9 | | -7-4u-u=0 | | -6x+5=23 | | 2.25x-9.45=x+3.28 | | 4x-6=3x-2 | | 9-b=59 | | 8u+2u-3u=43 | | -10(t-6)+11t-16=108 |

Equations solver categories